Specificities of Involving Small Enterprises into International S&T Co-operation: Evidence from the Linkages between Russia and Germany - Mikhail Gershman; Tatiana Kuznetsova (Foresight and STI Governance, 2012)
Institute for Statistical Studies and Economics of Knowledge, National Research University Higher School of Economics